Subhāshacandrera antarddhāna o tāra pratikriẏā - Rakshita, Nirmalendubikāśa (Ratnā, 1982)
On the disappearance of Subhas Chandra Bose, 1897-1945, Indian militant leader in the freedom movement, in 1941 and its effect on the contemporary political situation.